Unstable SpO2 in preterm infants: The key role of reduced ventilation to perfusion ratio - Stoecklin, Benjamin; Choi, Y. Jane; Dassios, Theodore; Jones, J. Gareth; Lockwood, Geoffrey G.; Pillow, J. Jane (Frontiers in Physiology, 2023)
Introduction Instability of peripheral oxyhemoglobin saturation (SpO2) in preterm infants is correlated with late disability and is poorly understood. We hypothesised that a reduced ventilation to perfusion ratio (VA/Q) is the key predisposing factor for SpO2 instability. Methods We first used a mathematical model to compare the effects of reduced VA/Q or shunt on SaO2 stability (SaO2 and SpO2 are used for model and clinical studies respectively). Stability was inferred from the slope of the SaO2 vs inspired oxygen pressure (PIO2) curve as it intersects the 21 kPa PIO2 line (breathing air). Then, in a tertiary neonatal intensive care unit, paired hourly readings of SpO2 and PIO2 were recorded over a 24 hour period in week old extremely preterm infants. We noted SpO2 variability and used an algorithm to derive VA/Q and shunt from the paired SpO2 and PIO2 measurements. Results Our model predicted that when VA/Q < 0.4, a 1% change in PIO2 results in > 8% fluctuation in SaO2 at 21kPa PIO2. In contrast, when a 20% intrapulmonary shunt was included in the model, a 1 % change in PIO2 results in < 1% fluctuation in the SaO2. Moreover, further reducing the VA/Q from 0.4 to 0.3 at 21 kPa PIO2 resulted in a 24% fall in SaO2. All 31 preterm infants (mean gestation (± SD) 26.2 (±1) week) had VA/Q <0.74 (normal >0.85) but only two infants had increased shunt at 1.1 (±0.5) weeks’ postnatal age. Median (IQR) SpO2 fluctuation was 8 (7) %. The greatest SpO2 fluctuations were seen in infants with VA/Q <0.52 (n=10): SpO2 fluctuations ranged from 11-17% at a constant PIO2 when VA/Q <0.52. Two infants had reduced VA/Q and increased shunt (21% and 27%) which resolved into low VA/Q after 3-6 hours. Discussion Routine monitoring of PIO2 and SpO2 can be used to derive a hitherto elusive measure of VA/Q. Predisposition to SpO2 instability results from reduced VA/Q rather than increased intrapulmonary shunt in preterm infants with cardiorespiratory disease.